Exchange rate volatility and tax revenue: Evidence from Ghana - Isaac Kwesi Ofori; Camara Kwasi Obeng; Mark Kojo Armah (Cogent Economics & Finance, 2018)
The need for the Ghanaian government to generate enough revenue for development is becoming increasingly crucial in this era of slow growth, growing unemployment, and high debt. However, tax revenue performance over the years reveals an unstable pattern. One key factor that has been overlooked in the literature in terms of the determinants of tax revenue is exchange rate volatility. Coming from the background of volatility in Ghana's exchange rate, could it be the reason for the instability in the trend of tax revenue? This question is the subject matter of this study. To estimate the effect of exchange rate volatility on tax revenue, the study employed the Auto Regressive Distributed Lag (ARDL) technique after the yearly exchange rate volatilities had been generated using the GARCH(1,1) method. The results of the study suggest that exchange rate volatility has a deleterious effect on tax revenue both in the short-run and long-run but the effect is more pronounced in the long-run than in the short-run. The study recommends that the bank of Ghana step-up its exchange rate stabilization efforts to reduce exchange rate risk imposed on international trade players.
Keywords: A10; E6; F1; F2; F3; F4; 330; Exchange rate volatility; GARCH; Tax revenue; Foreign aid; Ghana; Africa